PENGUKURAN KINERJA LAPORAN KEUANGAN MENGGUNAKAN ANALISIS RASIO PROFITABILITAS PADA PERUSAHAAN GO PUBLIC - Dedi Darwis; Meylinda Meylinda; Suaidah Suaidah (Universitas Teknokrat Indonesia, 2022)
Investment in shares is seen from the rise and fall of share prices on the Indonesia Stock Exchange (IDX), therefore, in investing in shares, investors must analyze the condition factors that affect the company. The stock price itself reflects the value of the stock to the public, a high stock price provides capital gains and a better image making it easier for management to get funds from outside the company. To measure and analyze a company, the main measuring tool is needed, namely the company's financial statements. Profitability is the result achieved by a company in a certain period, for example, at a certain level of sales, assets and share capital. This ratio is closely related to the ability and effectiveness of the company's operations in generating profits. Assessment of profitability ratios, namely the income statement and balance sheet (statement of financial position) which aims to measure the company's profit, both in relation to income, assets, and own capital. So the results of the profitability ratios are used as benchmarks or a description of the effectiveness of management performance seen from the profits obtained by the company. From the results of the analysis Profitability ratios in mining companies listed on the BEI can be seen in the company's financial performance based on the categories of very good, good, sufficient, less, and very poor. With the application of profitability ratio analysis, it can be seen how financial performance is, because the system can automatically calculate calculations for Profit Margin, Net Profit Margin, Return on Assets, Return on Equity. Users of this application can find out financial performance in order to minimize company losses in running a business.